Assessment of pollution at the former uranium waste dumpsite near kaji-Say Village/Kyrgyzstan: a genetic and physiological investigation - ÖZYİĞİT, İBRAHİM İLKER; SEVEROĞLU, ZEKİ (TAYLOR & FRANCIS LTD, 2021)
Kyrgyzstan still suffers from the past practices of radioactive industry operated by the Soviet Union that caused significant impact on ecosystems in this region, especially related with storage of uranium in inadequate conditions. There are at least 50 abandoned sites used as radioactive waste dumps in the country. Due to the pressure of natural and anthropogenic reasons, the structural foundations of mine waste dumps are gradually losing their integrities. Here, particular interest of our research is to reveal current state of radioactive contamination and to make evaluation on the radiological impacts of pollution caused by uranium mine waste dump, one is situated near Kaji-Say Village in Issyk Kul Region-Kyrgyzstan. In this study, the leaf, stem, and root parts of Perovskia abrotanoides Kar. and their co-located soils as study materials collected from five different localities were used for investigation of existent alterations on element uptake and genetic material in the plant using ICP-MS and ISSR marker technique. Also, radioactivity readings were recorded using Geiger counter. The data showed that the levels of radiation (in mR/h) were found to be significantly high in comparison with normal acceptable limits. Uptake patterns of certain elements in P. abrotanoides grown in the uranium waste dump site were modified extensively as reductions and increments due to strong radioactive leakage in comparison with the control. Also, the results indicated that changes in ISSR profiles from exposed plant leaf samples included variation in band intensities, losses of normal bands, and the appearances of new bands compared to unexposed (control) plant leaf sample. Considering people living around the area where the research was conducted, the consequences of contamination as our data suggest could cause health problems through radioactive leakage.
Keywords: Perovskia abrotanoides Kar; radioactive contamination; Kaji-say; Lake Issyk-kul; Kyrgyzstan; ISSYK-KUL; PEROVSKIA-ABROTANOIDES; IONIZING-RADIATION; HEAVY-METALS; MINING SITES; KADJI-SAI; LAKE; DAMAGE; LEVEL; IMPACT